The Concordantia of the three great sacramentaries: Gregorian, Veronese and Gelasian - Sodi, Manlio; Baroffio, Giacomo; Toniolo, Alessandro (Saeculum Christianum. Pismo Historyczne, 2021)
The “tradition” of the Church never ceases to amaze us with its wealth and the characteristics of its documents. The liturgical tradition contributes to this in an important way as well. Finding the appropriate tools to learn about these documents is of great importance. In this way, the great work done by the three scholars of liturgy is a beacon and an appeal. Looking through all of the texts reveals the infinity of elements which, without any shadow doubt, can be a great help per philolgiam ad theologia or ad culturam!